Decent work deficits in informal economy: case of Surat - Kantor, Paula; Unni, Jeemol; Uma Rani (2006)
This paper illustrates the challenges involved in achieving "decent work", as conceptualised by the International Labour Organisation, in the urban informal economy through measuring decent work deficits among male and female workers in Surat. It assesses and contributes to existing attempts to measure decent work and then examines the prevalence of deficits and inadequate earnings in Surat, disaggregating the analysis by structural insecurities shaping informal work opportunities in India, specifically gender and activity status. The results provide guidance regarding what types of policies are most needed, and for which groups, in order to achieve "decent work for all" in urban India. - Reproduced.
Keywords: Informal sector; Work environment